2018
DOI: 10.1099/mic.0.000646
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of a Pseudomonas aeruginosa sn-glycerol-3-phosphate dehydrogenase mutant reveals a disruption in bioenergetics

Abstract: Pseudomonas aeruginosa causes acute and chronic human infections and is the major cause of morbidity and mortality in cystic fibrosis (CF) patients. We previously determined that the sn-glycerol-3-phosphate dehydrogenase encoded by glpD plays a larger role in P. aeruginosa physiology beyond its role in glycerol metabolism. To better understand the effect of a glpD mutation on P. aeruginosa physiology we compared the transcriptomes of P. aeruginosa strain PAO1 and the PAO1ΔglpD mutant using RNA-seq analysis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Acetate and glycerol have different entry points into P. aeruginosa central carbon metabolism and also are thought to have distinct effects on redox metabolism (11)(12)(13)(14). We therefore anticipated a carbon source-specific impact on the expression of enzymes (and corresponding fluxes) involved in the relevant pathways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetate and glycerol have different entry points into P. aeruginosa central carbon metabolism and also are thought to have distinct effects on redox metabolism (11)(12)(13)(14). We therefore anticipated a carbon source-specific impact on the expression of enzymes (and corresponding fluxes) involved in the relevant pathways.…”
Section: Resultsmentioning
confidence: 99%
“…For the second and main cultures, PAO1 was grown in MOPS minimal media with 60 mM acetate or 40 mM glycerol as the sole carbon source (120 mM carbon). For 13 C flux experiments, naturally labeled acetate and glycerol were replaced with three separate tracers per carbon source to maximize data set resolution and to accurately determine substrate uptake. Naturally labeled glycerol was replaced with [1,[3][4][5][6][7][8][9][10][11][12][13] Starter cultures were prepared by inoculating LB medium with a loop of freshly plated PAO1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that glpD whose product Glycerol-3-phosphate (G3P) dehydrogenase catalyzes G3P transformation in the rpvA mutant is significantly increased, accompanied by a decrease in G3P and dihydroxyacetone phosphate (DHAP) compared with the wild type (Figure 14). Previous studies have confirmed that null mutations in glpD increased the persister formation in P. aeruginosa and E. coli (70, 71). GlpD and G3P synthase (GpsA) encoded by gpsA function at the juncture between respiration and glycolysis, and catalyze the interconversion of G3P and DHAP.…”
Section: Discussionmentioning
confidence: 62%
“…glpD encodes for a protein involved in glycerol metabolism. Mutations and changes its activity can affect the metabolism of amino acids, induce a stress response with rpoS[168], and lower alignate production making isolates much more virulent[169]. The R274H mutation was in only a single CF strain of PA and 38/639 non-CF strains.MetG, or methionyl-tRNA ligase, is required to initiate and elongate protein synthesis.…”
mentioning
confidence: 99%